Applying the Lewis Model in Industrialized Countries: W. Arthur Lewis and the Dual Economy of Manchester in the 1950s. (5th February 2015) - Mosley, Paul; Ingham, Barbara
Abstract : We document, for the first time, the institution‐building activities of the development economist W. Arthur Lewis (1915–91) as founder of Community House and the South Hulme Evening Centre, two further education centres which sought to fight discrimination among the Afro‐Caribbean communities of Manchester in the 1950s. We depict the struggle by Afro‐Caribbeans to achieve a decent standard of living (and to escape from the 'subsistence economy' which provides the basis for Lewis' most famous model) as a game of snakes and ladders in which the two main potential ladders out of poverty are—as in many developing countries—first, the ability to generate non‐wage income through self‐employment and second, 'vertical social capital', i.e. membership of social networks of a kind which gave the employee the ability to fight back against discrimination. The most imaginative aspect of Lewis's design for his further education centres is his incorporation of activities which build vertical social capital alongside conventional vocational training. On the basis of both the qualitative evidence and an exploratory model of the Manchester dual economy, we argue that Lewis' social centres had a significant positive impact on Afro‐Caribbean income and poverty levels, and that they still provide inspiration for development practitioners.